Implementation of Accounting Standards By SMEs: Coercion or Rationality? - Mila Indriastuti (Agregat: Jurnal Ekonomi dan Bisnis, 2022)
This study explores the implementation of SMEs Accounting Standard and observes its motives. The research method uses a narrative paradigm with an interview and observation approach. The results of this study showed that not all informants used SAK EMKM. The findings refute prior research that considers education, perception, and understanding of the motive of compliance with the standard. Moreover, rationality and stakeholder theory become the strong motives underlying their decision to implement SMEs Accounting Standard.